Oat β Glucan Ameliorates Renal Function and Gut Microbiota in Diabetic Rats - Wang, Ruoyu; Zhang, Zhaofeng; Aihemaitijiang, Sumiya; Ye, Chen; Halimulati, Mairepaiti; Huang, Xiaojie; Qin, Haoyuan (Frontiers in Nutrition, 2022)
Diabetic nephropathy is a severe complication of diabetes and the leading cause of end-stage renal disease and death. Therefore, we must find effective prevention and treatment approaches to the problem. Oat has a long history of use for its nutritional and medicinal properties, such as maintaining physiological blood glucose levels. Oat β glucan is one of the major bioactive substances produced by oat. However, the protective effects of oat β glucan on diabetic nephropathy are still unclear. This study generated a rat model of diabetic nephropathy to explore the potent therapeutic ability and mechanism of oat β glucan in renal function by 16S rRNA genes sequencing. Diabetic nephropathy model was established in forty rats by left nephrectomy and single intraperitoneal injection of streptozotcin. These rats were randomly divided into the model group and three oat β glucan intervention groups. Twenty rats underwent sham operation and were randomly divided into normal control group and oat β glucan control group. Animals were treated by oral gavage for 8 consecutive weeks. The results showed that oat β glucan reduced blood glucose level and improved renal function (P＜0.05). Oat β glucan significantly improved serum inflammatory levels (P＜0.05). The diversity of intestinal microflora in diabetic nephropathy rats decreased with time prolongation, while oat β-glucan reversed the result. Compared with the model group at week 8, the abundances of Eubacterium, Butyricicoccus, and Ruminococcus were elevated significantly after oat β glucan intervention (P＜0.05). Correlation analysis indicated that abundances of Eubacterium, Butyricicoccus, and Ruminococcus were significantly negatively correlated with the levels of renal impairment markers. In summary, the findings of this study showed that oat β glucan can increase the diversity of intestinal flora, regulate the composition of intestinal flora, modulate intestinal flora metabolism, alleviate the inflammatory response, and further delay the development of diabetic nephropathy. Therefore, oat β glucan has the potential to be developed into the novel and safe drug for diabetic nephropathy.